2022
DOI: 10.1556/063.2022.00118
|View full text |Cite
|
Sign up to set email alerts
|

Professional competencies and the continuing professional development needs of Technical, Vocational Education and Training (TVET) teachers in Kenya

Abstract: The development of Continuing Professional Development (CPD) programs for vocational teachers in Africa has been hampered by a lack of relevant research on their CPD practices and learning needs. This study therefore investigated the learning needs of vocational teachers in Kenya based on the professional competencies vocational teachers identify as essential for their work and their self-perception of competence. Using a concurrent mixed methods approach, data was collected from 170 questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These results are supported by research [17] that there is a positive and significant relationship between teacher participation in subject teacher conference and teacher professional competence. A relationship exists between participation in development programs and teacher professional performance [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are supported by research [17] that there is a positive and significant relationship between teacher participation in subject teacher conference and teacher professional competence. A relationship exists between participation in development programs and teacher professional performance [15].…”
Section: Resultsmentioning
confidence: 99%
“…Education and training positively and significantly affect professional competence and teacher performance [14]. There is a relationship between participation in development programs and the professional performance of teachers [15]. There is a non-significant influence on the competence of VHST in terms of the length of time they have attended the training [5].…”
Section: Self Developmentmentioning
confidence: 99%
“…Table 2 shows that the study informants met all criteria for being secondary school teachers in Tanzania [ 126 ]. Additionally [ 127 ], states that teachers who have worked for less than five years are at an early career stage, between six and twenty years are in the middle career, and more than twenty years are in the late career stage. However, for the sake of getting informants with sufficient narrative data on measures for better clinical supervision practices and predictive indicators in developing teachers' professional identity, teachers whose working experience was five years and above were the most preferred.…”
Section: Methodsmentioning
confidence: 99%
“…These conditions have resulted in a large number of TVET teachers lacking adequate professional competencies and expressing a strong need for TVET teacher CPD. Indeed (Njenga, 2022a), found that TVET teachers in Kenya express a relatively high need for professional development.…”
Section: Context Of the Studymentioning
confidence: 99%